Sensei No Kuruma : car advising system with digital forensic evidence - Mansor, Hafizah; Mohd Shani, Nur Shahirah Hafizah; Pradu, Arina (IIUM Press, 2021)
Drivers need to be well-aware of the conditions of their cars. Most drivers, especially women, are not well-versed in automotive systems and functionalities. On the other hand, there are now many available mobile applications to assist drivers in terms of navigation as well as car maintenance. However, most of these applications on car maintenance provide very technical information that are not user-friendly for laymen. Our newly developed application aims to solve this problem by providing the list of trouble codes, with their respective descriptions, and suggestions to fix the problems. Hence, it is called Sensei No Kuruma ("Car Teacher" - in Japanese word) to give advice to the drivers regarding their cars. The application will connect to the On-Board Diagnostic (OBD) port of the car using ELM327 via Bluetooth. Additionally, the application also records all the diagnostic sessions for further assessments, and has an extra feature for parents to be alert on the presence of their children in the car. These features are possible through real-time extraction of digital forensic evidence. This app could be useful for car owners and drivers to know the condition of their cars. Additionally, the logging of the data can be useful for forensic purposes.